Dual Effect of CTCF Loss on Neuroprogenitor Differentiation and Survival - Watson, L. Ashley (J Neurosci, 2014)
An increasing number of proteins involved in genome organization have been implicated in neurodevelopmental disorders, highlighting the importance of chromatin architecture in the developing CNS. The CCCTC-binding factor (CTCF) is a zinc finger DNA binding protein involved in higher-order chromatin organization, and mutations in the human CTCF gene cause an intellectual disability syndrome associated with microcephaly. However, information on CTCF function in vivo in the developing brain is lacking. To address this gap, we conditionally inactivated the Ctcf gene at early stages of mouse brain development. Cre-mediated Ctcf deletion in the telencephalon and anterior retina at embryonic day 8.5 triggered upregulation of the p53 effector PUMA (p53 upregulated modulator of apoptosis), resulting in massive apoptosis and profound ablation of telencephalic structures. Inactivation of Ctcf several days later at E11 also resulted in PUMA upregulation and increased apoptotic cell death, and the Ctcf-null forebrain was hypocellular and disorganized at birth. Although deletion of both Ctcf and Puma in the embryonic brain efficiently rescued Ctcf-null progenitor cell apoptosis, it failed to improve neonatal hypocellularity due to decreased proliferative capacity of rescued apical and outer radial glia progenitor cells. This was exacerbated by an independent effect of CTCF loss that resulted in depletion of the progenitor pool due to premature neurogenesis earlier in development. Our findings demonstrate that CTCF activities are required for two distinct events in early cortex formation: first, to correctly regulate the balance between neuroprogenitor cell proliferation and differentiation, and second, for the survival of neuroprogenitor cells, providing new clues regarding the contributions of CTCF in microcephaly/intellectual disability syndrome pathologies.